Analisis Dinamik Struktur Bangunan Gedung Yang Menggunakan Sistem Seismic Isolation Lead Rubber Bearing - Dwiyanto, Efri; Bayzoni, Bayzoni; Purwanto, Eddy (Universitas Lampung, 2017)
ndonesia is an archipelagic country that passes seismic path, so that earthquakes often occur. Earth vibrations caused by an earthquake, can vibrate the structure on it and cause deformation that can damage the structural building. One effort to reduce the damage is by using seismic isolation system. This system will separate the structure of the horizontal components of ground movement by inserting the base isolator. This study was conducted to examine the effect of using base isolator (lead rubber bearing) when compared with the building without using base isolator on the medium soil and soft soil. Interstory drift is calculated using the response spectrum method by manual and Software SAP2000. Results of the analysis showed that the use of base isolator increase the natural period of the structure so that it can decrease the interstory drift in the building. The maximum interstory drift at fix base and base isolation is 4,3335 mm and 0,5741 mm on medium soil, 6,8606 mm and 0,9139 mm in soft soil, respectively. The reduction of interstory drift in both soil type reached 91%. Keywords: Interstory drift, seismic isolation, lead rubber bearing, response spectrum, SAP2000.